The Involvement Locus of Control, Servant Leadership, and Innovative Work Behavior to Improve Teacher Performance - Silalahi, Marto; Abdurohim, Abdurohim; Romy, Elly; Candra, Vivi; Sudirman, Acai (Jurnal Pendidikan Progresif, 2022)
Objectives:The main objective of this study was to analyze the influence of the variables locus of control, servant leadership, and innovative work behavior on the performance of private high school teachers in Pematangsiantar City. Methods: This research uses a research design with a quantitative approach and online questionnaires distribute the research data. The sample used in the study were 110 respondents. The basis for determining the sample is oriented to the non-probability sampling approach by using the purposive sampling formula. Findings: The results of this research explain that locus of control, servant leadership, and innovative work behavior have a positive and significant effect on teacher performance. Conclusion: The findings of this study confirm that the better the role of locus of control will have implications for the resulting better performance. In addition, innovative work behavior when carrying out duties as a teacher reflects the teacher's ability to manage optimal performance.Keywords: teacher performance, locus of control, servant leadership, innovative work behavior.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202227